Alumina fiber reinforced polylactic acid composite material and polylactic acid yarn made therefrom

By modifying alumina fiber, it improves the compatibility and anti -static performance of polylactic acid, solve the problem of incomplete dispersing alumina fiber in polymapilic acid composite materials, significantly improves the mechanical performance of polystrackic acid fiber , Flame retardant performance and heat resistance, and simplify process operations.

CN116041922BActive Publication Date: 2025-01-24ANHUI ZHENGXIN BIOTECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211605703.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2025-01-24
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

The poor interface compatibility between alumina fibers and polylactic acid leads to uneven dispersion of alumina fibers in the polylactic acid composite material, affecting the mechanical properties, flame retardant properties and heat resistance of polylactic acid.

Method used

Modified by alumina fiber, reacting the use of polypholic glycol and tritethylocyanate reactions to generate trimer siliconal aminamine polyetal glycols, modified aluminum fiber compatibility with polylactal acid , Improve the anti -static performance of alumina fiber.

Benefits of technology

Modified aluminum fiber can better play an enhanced role in polystumin composite materials, significantly improve the mechanical properties, flame retardant performance, and heat resistance of polystumin fiber, while reducing the addition of antistatic agents, simplifying process operations and reducing processing processing cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003998850530000071
    Figure BDA0003998850530000071
Patent Text Reader

Abstract

The invention discloses an alumina fiber reinforced polylactic acid composite material and a polylactic acid yarn made thereof, and relates to the technical field of polylactic acid composite materials. Aiming at the problem of poor interface compatibility between commercially available alumina fibers and polylactic acid, the invention improves the affinity between the alumina fibers and polylactic acid by modifying the alumina fibers, thereby enabling the alumina fibers to fully exert their reinforcing effect, optimizing the mechanical properties, flame retardant properties and heat resistance of the prepared polylactic acid fibers; at the same time, the antistatic properties of the alumina fiber reinforced polylactic acid composite material are improved, thereby solving the problem that the alumina fibers are prone to generate static electricity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of polylactic acid composite materials, and in particular to an alumina fiber reinforced polylactic acid composite material and a polylactic acid yarn made thereof. Background technology:

[0002] Polylactic acid, also known as polylactide, is a polyester polymer obtained by polymerization of lactic acid as the main raw material. It is a bio-based degradable material. Polylactic acid has good thermal stability and a processing temperature of 170-230°C. It can be processed in a variety of ways, such as extrusion, spinning, biaxial stretching, and injection blow molding. In addition to being biodegradable, products made of polylactic acid have good biocompatibility, gloss, transparency, feel, and heat resistance.

[0003] However, compared with traditional engineering plastics, the mechanical properties and heat resistance of polylactic acid materials are poor, so modification methods are often used to improve the comprehensive performance of polylactic acid materials. The modification methods of polylactic acid mainly include blending modification, cross-linking modification, copolymerization modification and grafting modification. Among them, blending modification is easy to operate, and only requires fully mixing polylactic acid and fillers. Fillers include inorganic fillers, organic fillers and composite fillers. Compared with organic fillers, the interface compatibility between inorganic fillers and polylactic acid is poor. It is impossible to evenly disperse inorganic fillers in polylactic acid by simple mixing, which will affect the modification effect of inorganic fillers on polylactic acid. Summary of the invention:

[0004] The technical problem to be solved by the present invention is to provide a method for preparing an alumina fiber reinforced polylactic acid composite material, by adding modified alumina fibers to substantially improve the mechanical properties, flame retardant properties, heat resistance and antistatic properties of polylactic acid fibers, thereby comprehensively improving the use effect of polylactic acid yarns made from the polylactic acid fibers.

[0005] One of the purposes of the present invention is to provide an alumina fiber reinforced polylactic acid composite material, which is prepared by the following steps:

[0006] (1) drying the alumina fiber, adding polyethylene glycol, trimethylsilyl isocyanate and a catalyst, heating for reaction, cooling after the reaction, crushing and grinding to obtain modified alumina fiber;

[0007] (2) The polylactic acid is dried, and then mixed evenly with the modified alumina fiber prepared above, and then melt-extruded using a twin-screw extruder, cooled, granulated, and dried to obtain an alumina fiber-reinforced polylactic acid composite material.

[0008] In the present invention, trimethylsilylcarbamate polyethylene glycol is generated in situ in alumina fibers by the reaction of polyethylene glycol and trimethylsilyl isocyanate. The obtained modified alumina fibers not only have good compatibility with polylactic acid, but also can improve the antistatic properties of the alumina fibers, thereby enabling the alumina fibers to better exert their reinforcing properties in polylactic acid composite materials.

[0009] Preferably, the drying temperature is 80-100° C. to reduce the water content to less than 200 ppm.

[0010] Preferably, the molecular weight of the polyethylene glycol is 1000-4000.

[0011] Preferably, the mass ratio of the alumina fiber to polyethylene glycol and trimethylsilyl isocyanate is 50:(30-50):(5-20).

[0012] Preferably, the catalyst is an organic bismuth catalyst, and the amount used is 0.1-1% of the total mass of polyethylene glycol and trimethylsilyl isocyanate.

[0013] Preferably, the number average molecular weight of the polylactic acid is 50,000-300,000.

[0014] Preferably, the mass ratio of the polylactic acid to the modified alumina fiber is 100:(20-40).

[0015] Preferably, the temperature of the twin-screw extruder is 150-200°C, the screw speed is 100-350r / min, and the screw aspect ratio is (36-52):1.

[0016] The main component of alumina fiber is alumina, which has poor compatibility with polylactic acid. When alumina fiber is directly added to polylactic acid, agglomeration is likely to occur, which cannot effectively improve the mechanical properties, flame retardancy and heat resistance of polylactic acid. Therefore, it is necessary to modify the alumina fiber to improve its uniformity of dispersion in polylactic acid. Currently, the commonly used modification method is to coat and modify the alumina fiber with a coupling agent, but the present invention does not adopt this method, but uses polyethylene glycol and trimethylsilyl isocyanate as modifiers, and the trimethylsilyl carbamate polyethylene glycol ester generated in situ by condensation reaction is used to coat and modify the alumina fiber, which can achieve a modification effect far superior to that of the coupling agent.

[0017] The second object of the present invention is to provide a polylactic acid fiber, comprising polylactic acid and the alumina fiber reinforced polylactic acid composite material.

[0018] Preferably, the mass ratio of the polylactic acid to the alumina fiber reinforced polylactic acid composite material is 100:(30-50).

[0019] The third object of the present invention is to provide a method for preparing the polylactic acid fiber, wherein polylactic acid and alumina fiber reinforced polylactic acid composite material are uniformly mixed and then melt-spun, wound, drawn, and heat-set to obtain polylactic acid fiber.

[0020] Preferably, the melt spinning temperature is 200-240°C, the winding speed is 1500-2500 m / min, the drawing temperature is 90-120°C, the drawing ratio is 2-5, and the heat setting temperature is 100-130°C.

[0021] A fourth object of the present invention is to provide application of the polylactic acid fiber in polylactic acid yarn processing.

[0022] The fifth object of the present invention is to provide a polylactic acid fiber, comprising polylactic acid, the alumina fiber reinforced polylactic acid composite material and aluminum acetylacetonate. The antistatic property of the polylactic acid fiber is improved by adding aluminum acetylacetonate.

[0023] Preferably, the mass ratio of the polylactic acid, the alumina fiber reinforced polylactic acid composite material, and aluminum acetylacetonate is 100:(30-50):(0.5-2).

[0024] The sixth object of the present invention is to provide a method for preparing the polylactic acid fiber, wherein polylactic acid, alumina fiber reinforced polylactic acid composite material and aluminum acetylacetonate are uniformly mixed and then melt-spun, wound, drawn and heat-set to obtain polylactic acid fiber.

[0025] Preferably, the melt spinning temperature is 200-240°C, the winding speed is 1500-2500 m / min, the drawing temperature is 90-120°C, the drawing ratio is 2-5, and the heat setting temperature is 100-130°C.

[0026] The beneficial effects of the present invention are as follows: the present invention aims at the problem of poor interface compatibility between commercially available alumina fibers and polylactic acid, and improves the affinity between alumina fibers and polylactic acid by modifying the alumina fibers, so that the alumina fibers can fully exert their reinforcing effect, and optimize the mechanical properties, flame retardant properties and heat resistance of the prepared polylactic acid fibers; at the same time, the antistatic properties of the alumina fiber-reinforced polylactic acid composite materials are improved, and the problem that alumina fibers are prone to generate static electricity is solved, thereby reducing the amount of antistatic agent added to the polylactic acid fibers, and even not adding the antistatic agent when the antistatic performance requirements are not high, thereby simplifying the process operation and reducing the processing cost. Specific implementation method:

[0027] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0028] The polylactic acid in the following examples and comparative examples was purchased from the same batch of polylactic acid resins from Zhejiang Hisun Biomaterials Co., Ltd.

[0029] Example 1

[0030] 1. Preparation of alumina fiber reinforced polylactic acid composite materials:

[0031] (1) Alumina fiber is dried at 80° C. to reduce the water content to less than 200 ppm, and then polyethylene glycol 2000, trimethylsilyl isocyanate and organic bismuth catalyst DY-20 are added to the alumina fiber, and the mixture is heated to 80° C. for reaction until the relative density of the system does not change within 30 minutes. After the reaction is completed, the mixture is cooled, crushed and ground to obtain modified alumina fiber; wherein the mass ratio of alumina fiber to polyethylene glycol and trimethylsilyl isocyanate is 50:40:15, based on the dry weight of alumina fiber; and the amount of organic bismuth catalyst DY-20 is 0.5% of the total mass of polyethylene glycol and trimethylsilyl isocyanate.

[0032] (2) Drying the polylactic acid at 80°C to reduce the water content to less than 200 ppm, then uniformly mixing it with the modified alumina fiber prepared above, and then melt-extruded by a twin-screw extruder, cooled, granulated, and dried to obtain an alumina fiber reinforced polylactic acid composite material. The mass ratio of polylactic acid to modified alumina fiber is 100:30; the set temperatures of the twin-screw extruder from the feeding section to the die are 150°C, 155°C, 160°C, 170°C, 180°C, 185°C, 190°C, 195°C, 200°C, and 195°C, respectively; the screw speed is 150 r / min; and the screw aspect ratio is 36:1.

[0033] 2. Preparation of polylactic acid fiber:

[0034] The polylactic acid and alumina fiber reinforced polylactic acid composite material are mixed evenly, melt-spun, wound, drawn, and heat-set to obtain polylactic acid fiber. The mass ratio of polylactic acid to alumina fiber reinforced polylactic acid composite material is 100:40; the melt spinning temperature is 220°C, the winding speed is 1500m / min, the drawing temperature is 100°C, the drawing ratio is 3, and the heat setting temperature is 120°C.

[0035] Example 2

[0036] 1. Preparation of alumina fiber reinforced polylactic acid composite materials:

[0037] (1) Alumina fiber is dried at 100° C. to reduce the water content to less than 200 ppm, and then polyethylene glycol 1000, trimethylsilyl isocyanate and organic bismuth catalyst DY-20 are added to the alumina fiber, and the mixture is heated to 80° C. for reaction until the relative density of the system does not change within 30 minutes. After the reaction is completed, the alumina fiber is cooled, crushed and ground to obtain modified alumina fiber; wherein the mass ratio of alumina fiber to polyethylene glycol and trimethylsilyl isocyanate is 50:30:10, based on the dry weight of the alumina fiber; and the amount of the organic bismuth catalyst DY-20 is 0.5% of the total mass of polyethylene glycol and trimethylsilyl isocyanate.

[0038] (2) Drying the polylactic acid at 100°C to reduce the water content to less than 200 ppm, then uniformly mixing it with the modified alumina fiber prepared above, and then melt-extruded by a twin-screw extruder, cooled, granulated, and dried to obtain an alumina fiber reinforced polylactic acid composite material. The mass ratio of polylactic acid to modified alumina fiber is 100:20; the set temperatures of the twin-screw extruder from the feeding section to the die are 150°C, 155°C, 160°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, and 195°C, respectively; the screw speed is 200 r / min; and the screw aspect ratio is 48:1.

[0039] 2. Preparation of polylactic acid fiber:

[0040] The polylactic acid and alumina fiber reinforced polylactic acid composite material are mixed evenly, melt-spun, wound, drawn, and heat-set to obtain polylactic acid fiber. The mass ratio of polylactic acid to alumina fiber reinforced polylactic acid composite material is 100:50; the melt spinning temperature is 225°C, the winding speed is 2000m / min, the drawing temperature is 90°C, the drawing ratio is 3.5, and the heat setting temperature is 120°C.

[0041] Example 3

[0042] 1. Preparation of alumina fiber reinforced polylactic acid composite materials:

[0043] (1) Alumina fiber is dried at 90° C. to reduce the water content to less than 200 ppm, and then polyethylene glycol 4000, trimethylsilyl isocyanate and organic bismuth catalyst DY-20 are added to the alumina fiber, and the mixture is heated to 80° C. for reaction until the relative density of the system does not change within 30 minutes. After the reaction is completed, the mixture is cooled, crushed and ground to obtain modified alumina fiber; wherein the mass ratio of alumina fiber to polyethylene glycol and trimethylsilyl isocyanate is 50:50:20, based on the dry weight of alumina fiber; and the amount of organic bismuth catalyst DY-20 is 0.3% of the total mass of polyethylene glycol and trimethylsilyl isocyanate.

[0044] (2) Drying the polylactic acid at 90°C to reduce the water content to less than 200 ppm, then uniformly mixing it with the modified alumina fiber prepared above, and then melt-extruded by a twin-screw extruder, cooled, granulated, and dried to obtain an alumina fiber reinforced polylactic acid composite material. The mass ratio of polylactic acid to modified alumina fiber is 100:30; the set temperatures of the twin-screw extruder from the feeding section to the die are 150°C, 155°C, 160°C, 170°C, 180°C, 185°C, 190°C, 190°C, 200°C, and 195°C, respectively; the screw speed is 150 r / min; and the screw aspect ratio is 52:1.

[0045] 2. Preparation of polylactic acid fiber:

[0046] The polylactic acid and alumina fiber reinforced polylactic acid composite material are mixed evenly, melt-spun, wound, drawn, and heat-set to obtain polylactic acid fiber. The mass ratio of polylactic acid to alumina fiber reinforced polylactic acid composite material is 100:35; the melt spinning temperature is 230°C, the winding speed is 1500m / min, the drawing temperature is 100°C, the drawing ratio is 3, and the heat setting temperature is 130°C.

[0047] Example 4

[0048] 1. Preparation of alumina fiber reinforced polylactic acid composite materials:

[0049] (1) Alumina fiber is dried at 100° C. to reduce the water content to less than 200 ppm, and then polyethylene glycol 2000, trimethylsilyl isocyanate and organic bismuth catalyst DY-20 are added to the alumina fiber, and the mixture is heated to 80° C. for reaction until the relative density of the system does not change within 30 minutes. After the reaction is completed, the alumina fiber is cooled, crushed and ground to obtain modified alumina fiber; wherein the mass ratio of alumina fiber to polyethylene glycol and trimethylsilyl isocyanate is 50:45:15, based on the dry weight of the alumina fiber; and the amount of the organic bismuth catalyst DY-20 is 0.5% of the total mass of polyethylene glycol and trimethylsilyl isocyanate.

[0050] (2) Drying the polylactic acid at 100°C to reduce the water content to less than 200 ppm, then uniformly mixing it with the modified alumina fiber prepared above, and then melt-extruded by a twin-screw extruder, cooled, granulated, and dried to obtain an alumina fiber reinforced polylactic acid composite material. The mass ratio of polylactic acid to modified alumina fiber is 100:40; the set temperatures of the twin-screw extruder from the feeding section to the die are 150°C, 155°C, 160°C, 170°C, 185°C, 190°C, 195°C, 195°C, 200°C, and 195°C, respectively; the screw speed is 250 r / min; and the screw aspect ratio is 36:1.

[0051] 2. Preparation of polylactic acid fiber:

[0052] The polylactic acid and alumina fiber reinforced polylactic acid composite material are mixed evenly, melt-spun, wound, drawn, and heat-set to obtain polylactic acid fiber. The mass ratio of polylactic acid to alumina fiber reinforced polylactic acid composite material is 100:30; the melt spinning temperature is 230°C, the winding speed is 2000m / min, the drawing temperature is 90°C, the drawing ratio is 2.5, and the heat setting temperature is 130°C.

[0053] Example 5

[0054] Example 5 The method for preparing alumina fiber reinforced polylactic acid composite materials and polylactic acid fibers is the same as that of Example 1, except that aluminum acetylacetonate is added when preparing the polylactic acid fibers, and the mass ratio of polylactic acid to aluminum acetylacetonate is 100:0.5.

[0055] Example 6

[0056] Example 6 The method for preparing alumina fiber reinforced polylactic acid composite materials and polylactic acid fibers is the same as that of Example 1, except that aluminum acetylacetonate is added when preparing the polylactic acid fibers, and the mass ratio of polylactic acid to aluminum acetylacetonate is 100:1.

[0057] Comparative Example 1

[0058] Comparative Example 1 The method for preparing alumina fiber reinforced polylactic acid composite material and polylactic acid fiber is the same as that of Example 1, except that the modified alumina fiber is prepared by the following method:

[0059] The alumina fiber is dried at 80°C to make the water content less than 200 ppm, and then γ-aminopropyltriethoxysilane is added to the alumina fiber, and the fiber is heated to 80°C for reaction until the relative density of the system does not change within 30 minutes. After the reaction, the fiber is cooled, crushed, and ground to obtain modified alumina fiber; wherein the mass ratio of alumina fiber to γ-aminopropyltriethoxysilane is 50:55.

[0060] Comparative Example 2

[0061] Comparative Example 2 The method for preparing alumina fiber reinforced polylactic acid composite material and polylactic acid fiber is the same as that of Example 1, except that the modified alumina fiber is prepared by the following method:

[0062] The alumina fiber is dried at 80°C to make the water content less than 200 ppm, and then 3-isocyanatepropyltriethoxysilane is added to the alumina fiber, and the fiber is heated to 80°C for heat preservation and reaction until the relative density of the system does not change within 30 minutes. After the reaction is completed, the fiber is cooled, crushed, and ground to obtain modified alumina fiber; wherein the mass ratio of the alumina fiber to 3-isocyanatepropyltriethoxysilane is 50:55.

[0063] Comparative Example 3

[0064] Comparative Example 3: The method for preparing alumina fiber reinforced polylactic acid composite material and polylactic acid fiber is the same as that of Example 1, except that the alumina fiber is not modified.

[0065] The single-filament strength and single-filament elongation at break of the polylactic acid fibers prepared in the above-mentioned embodiments and comparative examples were tested using a universal testing machine (Model 3400, Instron, USA). The results are shown in Table 1.

[0066] Table 1

[0067]

[0068] It can be seen from Table 1 that the alumina fiber modification method adopted in the present invention can substantially improve the mechanical strength of polylactic acid fiber, and the modification effect is significantly better than the silane coupling agent modification method commonly used in the art.

[0069] The polylactic acid fibers prepared in the above examples and comparative examples were spun into polylactic acid yarns, warped to obtain warp yarns and weft yarns, and woven to obtain polylactic acid fabrics. The charge surface density test was performed in accordance with the national standard GB / T 12703.2-2021, and the results are shown in Table 2. The smaller the charge surface density, the better the antistatic performance.

[0070] Table 2

[0071] <![CDATA[Surface charge density (uc / m 2 )]]> Example 1 0.53 Example 2 0.61 Example 3 0.49 Example 4 0.58 Example 5 0.40 Example 6 0.32 Comparative Example 1 3.27 Comparative Example 2 3.49 Comparative Example 3 6.85

[0072] It can be seen from Table 2 that the alumina fiber modification method adopted in the present invention can substantially improve the antistatic properties of polylactic acid fabrics, and the modification effect is significantly better than the silane coupling agent modification method commonly used in the art; and adding a small amount of aluminum acetylacetonate can further improve the antistatic properties of polylactic acid fabrics.

[0073] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An alumina fiber reinforced polylactic acid composite material, characterized in that: Prepared by the following steps: (1) drying the alumina fiber, adding polyethylene glycol, trimethylsilyl isocyanate and a catalyst, heating for reaction, cooling after the reaction, crushing and grinding to obtain modified alumina fiber; (2) drying the polylactic acid, then uniformly mixing it with the modified alumina fiber prepared above, and then melt-extruding it using a twin-screw extruder, cooling, granulating, and drying to obtain an alumina fiber reinforced polylactic acid composite material; The mass ratio of the alumina fiber to polyethylene glycol and trimethylsilyl isocyanate is 50:(30-50):(5-20); The catalyst is an organic bismuth catalyst, and the amount used is 0.1-1% of the total mass of polyethylene glycol and trimethylsilyl isocyanate.

2. The alumina fiber reinforced polylactic acid composite material according to claim 1, characterized in that: The drying temperature is 80-100° C. to make the water content lower than 200 ppm.

3. The alumina fiber reinforced polylactic acid composite material according to claim 1, characterized in that: The mass ratio of the polylactic acid to the modified alumina fiber is 100:(20-40).

4. The alumina fiber reinforced polylactic acid composite material according to claim 1, characterized in that: The temperature of the twin-screw extruder is 150-200° C., the screw speed is 100-350 r / min, and the screw aspect ratio is (36-52):

1.

5. A polylactic acid fiber, comprising polylactic acid and the alumina fiber reinforced polylactic acid composite material according to any one of claims 1 to 4.

6. The polylactic acid fiber according to claim 5, characterized in that: The mass ratio of the polylactic acid to the alumina fiber reinforced polylactic acid composite material is 100:(30-50).

7. The method for preparing polylactic acid fiber according to claim 5, characterized in that: The polylactic acid and alumina fiber reinforced polylactic acid composite material are uniformly mixed, melt-spinned, wound, drawn, and heat-set to obtain polylactic acid fiber; The temperature of the melt spinning is 200-240°C, the winding speed is 1500-2500m / min, the drawing temperature is 90-120°C, the drawing ratio is 2-5, and the heat setting temperature is 100-130°C.

8. Use of the polylactic acid fiber according to claim 5 in polylactic acid yarn processing.

Citation Information

Patent Citations

  • Thermoplastic resin composition and molded body obtained by molding the same

    CN101896551A

  • Preparation method of fully-degradable foamed plastic

    CN104788979A

  • Silica-surface modified alpha-alumina whiskers and uses thereof

    CN105358630A

  • Polylactic acid fiber and its production

    JP1996226016A